Acute Cholecystitis: An Update - Kumar Hari Rajah (Recent Updates in Disease and Health Research Vol. 9, 2024)
Acute cholecystitis is a complication of gallstone disease, and its severity can be graded according to the Tokyo Guidelines into grades one, two, and three. The management of acute cholecystitis can be divided into conservative treatment followed by delayed cholecystectomy. With the introduction of laparoscopic cholecystectomy, early cholecystectomy has slowly emerged as the treatment of choice. As there is no consensus on the management of acute cholecystitis, this chapter investigates the role of conservative treatment, timing of laparoscopic cholecystectomy and the role of percutaneous cholecystostomy.